An experimental study on four-directional intersecting pedestrian flows. (26th August 2015) - Lian, Liping; Mai, Xu; Song, Weiguo; Kit Richard, Yuen Kwok; Wei, Xiaoge; Ma, Jian
Abstract: Intersecting pedestrian flows especially multi-directional ones are complicated in dynamics. People will face unavoidable head-on conflicts and obstruct each other. In this paper, controlled experiments of a four-directional intersecting pedestrian flow were conducted. Up to 364 university students took part in the experiments and their trajectories were extracted by a mean-shift algorithm. The global density–velocity relations in the cross area in different scenarios are compared. Moreover, local density–velocity and local density-flow relations in the cross area are investigated. In order to adapt the study of a fundamental diagram for four directional intersecting flows, a new coordinate system based on pedestrian motion is built. The results indicate that the coordinate system is suitable for the analysis of multi-directional flows. The local density–velocity relation seems consistent with previous results obtained from an actual high-density pedestrian flow. At high densities, the average local velocity in the cross area is a bit larger than a previous study. The reason may be due to the density difference between the cross area and the corridors, which can be observed in real life.